Update on the pathogenesis of endometriosis-related infertility based on contemporary evidence - Qi, Qing; Li, Yaonan; Chen, Ziqin; Luo, Zhihui; Zhou, Ting; Zhou, Jing; Zhang, Yanlin; Chen, Song; Wang, Ling (Frontiers in Endocrinology, 2025)
Endometriosis, the most prevalent cause of infertility, is associated with anatomical distortion leading to adhesions and fibrosis, as well as endocrine abnormalities and immune disorders. This review discusses the mechanisms underlying endometriosis-related infertility. Firstly, alterations in the hypothalamic-pituitary-ovarian axis lead to the secretion of gonadotropins and steroid hormones, with adverse effects on ovulation and implantation, leading to fertility decline. Secondly, dysregulation of the hypothalamic-pituitary-adrenal axis induces elevated serum cortisol and prolactin levels in patients with endometriosis, accounting for its regulation of stress, depression, and anxiety. Abnormal interactions between endometrial cells and the immune system change the local microenvironment, resulting in epithelial-mesenchymal transition and inflammation. Activated epithelial cells, stromal cells, and immunocytes produce various chemokines, cytokines, or autoantibodies, creating an unfavorable environment for embryo implantation. These findings suggest that alterations in the immune spectrum play a crucial role in endometriosis-related infertility. Thirdly, oxidative stress has adverse effects on the ovarian reserve and subsequent embryonic development, predicting another promising strategy for endometriosis-related infertility. An unbalanced redox state, including impaired mitochondrial function, dysregulated lipid metabolism, and iron-induced oxidative stress, generates a pro-oxidative microenvironment, which negatively impacts oocyte quality and sperm and embryo viability. Thus, an updated understanding of the mechanisms involved in this disease will help to develop effective strategies to manage endometriosis-related infertility.